1977
DOI: 10.1111/j.1744-313x.1977.tb00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Interactions of Virus Specific Effector Cells With Virus Infected Targets of Different Cell Type*

Abstract: SUMMARY The action of Sendai virus specific cytolytic T lymphocytes (CTL) against Sendai virus infected macrophages was found to be H‐2 restricted while Sendai virus infected cell lines, including fibroblasts and tumour cells, were lysed across the H‐2 barrier to some extent. The properties of the Meth‐A tumour cell, which was resistant to lysis by allogenic killer cells was investigated. Sendai virus specific CTL failed to kill Sendai virus infected Meth‐A cells but after vaccinia virus infection these target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1977
1977
1980
1980

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Virussensitized mouse T lymphocytes will only lyse target cells infected with related or homologous virus preparations if both effector and target cells share the K or D region of the H-2 gene complex, or both, and express the respective gene products. This observation has been described by many authors (10, 12,13,15,16,22,23,30,34,43,44). The assay systems usually involve a short-term incubation period (around 4 h) for the effector and target cell mixture and absence of active complement.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Virussensitized mouse T lymphocytes will only lyse target cells infected with related or homologous virus preparations if both effector and target cells share the K or D region of the H-2 gene complex, or both, and express the respective gene products. This observation has been described by many authors (10, 12,13,15,16,22,23,30,34,43,44). The assay systems usually involve a short-term incubation period (around 4 h) for the effector and target cell mixture and absence of active complement.…”
Section: Resultsmentioning
confidence: 66%
“…The aim of this study was to provide the means for measuring T-and B-cell responses in parallel in an easy way using the same assay system. It has been amply demonstrated that in mice antiviral activity of cytotoxic T cells is restricted by products of the major histocompatibility gene complex, H-2 (10,12,13,15,16,22,23,30,34,43,44), whereas cytolytic activity of B-cell products is not. Use of H-2-identical or -different effector-target combinations in the assay should allow discrimination between both types of responses.…”
mentioning
confidence: 99%